Amphibole in vermiculite mined in Argentina - Lescano, Leticia (2013)
Vermiculites with impurities of amphibole, a dry fine residue and calcined materials from three deposits in the province of Co´rdoba, Argentina, were studied. From a commercial perspective, amphiboles are considered as ‘‘asbestos’’, a group of silicate minerals with strong and flexible fibres that are heat resistant and chemically inert, and thus well suited for heat insulation. These fibrous particles have provoked controversies about the toxicity impact on human health and the development of diseases such as mesothelioma, asbestosis or lung cancer. Their commercialization and exploitation are currently prohibited. The sampled minerals were identified with a petrographic microscope, chemical analyses, SEM and XRD. It was concluded that amphibole minerals are present in all the deposits studied and in every phase of plant production, but not all of them have asbestiform characteristics.